PARTISIPASI POLITIK GENERASI MUDA: STUDI KUALITATIF PADA MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA - Fadiyah, Najwa; Mujab, Saeful (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to understand the forms, motivations, and barriers to political participation among young people in Indonesia's democratic governance system, focusing on students at Bhayangkara University, Jakarta Raya. A descriptive qualitative approach was used through interviews and observations. The subjects were active students from various study programs, particularly those involved in student organizations such as the Student Executive Board (BEM), the Departmental Student Association (Himpunan Mahasiswa Departemen), and non-organizational students as a comparison. The data used in this study were primary and secondary. Primary data was obtained through direct observation and documentation of student activities related to campus politics and responses to national issues. Secondary data came from scientific journals, academic articles, national survey reports (such as those from LIPI, KPU, BPS), and campus archives relevant to student political activity.This study found that students tend to be more active in non-conventional political participation such as social media campaigns, public discussions, and social movements. Their primary motivation is awareness of social issues and a desire for change. However, challenges such as apathy, lack of political education, and distrust of political institutions remain obstacles. This study emphasizes the need to strengthen relevant and participatory political education on campus. The results of this study are expected to contribute to designing strategies to increase political participation among young people more effectively and sustainably in Indonesia's democratic life. ABSTRAK Penelitian ini bertujuan untuk memahami bentuk, motivasi, dan hambatan partisipasi politik generasi muda dalam sistem pemerintahan demokratis di Indonesia, dengan fokus pada mahasiswa Universitas Bhayangkara Jakarta Raya. Menggunakan pendekatan kualitatif deskriptif melalui wawancara dan observasi. Subjek penelitian difokuskan pada mahasiswa aktif dari berbagai program studi, terutama yang tergabung dalam organisasi kemahasiswaan seperti BEM, Himpunan Mahasiswa Jurusan, serta mahasiswa non-organisatoris sebagai pembanding. Jenis data yang digunakan dalam penelitian ini adalah data primer dan sekunder. Data primer diperoleh observasi dan dokumentasi langsung terhadap aktivitas mahasiswa terkait politik kampus maupun respons terhadap isu nasional. Data sekunder bersumber dari jurnal ilmiah, artikel akademik, laporan survei nasional (seperti LIPI, KPU, BPS), serta arsip kampus yang relevan dengan aktivitas politik mahasiswa. Penelitian ini menemukan bahwa mahasiswa cenderung lebih aktif dalam partisipasi politik non-konvensional seperti kampanye media sosial, diskusi publik, dan gerakan sosial. Motivasi utama mereka adalah kesadaran terhadap isu sosial dan keinginan akan perubahan. Namun, tantangan seperti apatisme, kurangnya pendidikan politik, serta ketidakpercayaan terhadap institusi politik masih menjadi penghambat. Studi ini menekankan perlunya penguatan pendidikan politik yang relevan dan partisipatif di lingkungan kampus. Hasil penelitian ini diharapkan menjadi kontribusi dalam merancang strategi peningkatan partisipasi politik generasi muda secara lebih efektif dan berkelanjutan dalam kehidupan demokrasi di Indonesia.